Depiction of Mental Illness in The Yellow Wallpaper - Pokorná, Alexandra (Univerzita Pardubice, 2013)
This bachelor paper aims to present a thorough analysis of the mental illness depicted in the The Yellow Wallpaper by Charlotte Perkins Gilman. The theoretical part of this paper contains essential background knowledge of the 19th century American society especially in terms of gender stratification and perception of women's mental health and illness. The following section focuses on application of this knowledge to The Yellow Wallpaper with an intention to examine the image of insanity in Gilman's narrative. The paper also provides an explanation of the changing interpretation and perception of the story throughout history.
Zobrazení duševní poruchy v díle "Žlutá tapeta"
Keywords: Žlutá tapeta; Gilman, Charlotte Perkins; 19. století; mentální poruchy; deprese; hysterie; poporodní deprese; Yellow Wallpaper; True Womanhood; mental illness; depression; postpartum depression; madness; 19th century; madwoman in the attic